Synthesis of Blue Copper Sulfate Nanoparticles by Cold Plasma and Application to Bacteria - Hamid, Akram Muhammad; Hashem, Ahmed Salah; Suleiman, Mohsen Hadi; Hammadi, Ali Saleh Fahd (American Journal of Biology and Natural Sciences, 2024)
This research aims to prepare copper sulfate nanoparticles (CuSO4 NPs) experimentally by cold plasma method at a fixed concentration. Some tests and optical techniques have been performed for, ultraviolet-visible spectroscopy (UV-VIS), field emission scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy). The effect of the prepared nanoparticles on two types of bacteria: Escherichia coli and Staphylococcus aureus was studied. The results showed that nanoparticles prepared at a fixed concentration (2) mM at different exposure times (3 and 4) min had a polycrystalline cubic structure for all samples. In addition, the average crystal size changes directly with the change in exposure time to plasma at a fixed concentration (2). mM. On the other hand, the study showed that Gram-negative bacteria (Escherichia coli) were more resistant to the prepared copper sulfate nanoparticles. In contrast, Gram-positive bacteria (Staphylococcus aureus) were more affected by the prepared nanomaterial.